Neuro-Oncology Clinical Debate: PCV or temozolomide in combination with radiation for newly diagnosed high-grade oligodendroglioma. Issue 1 (3rd November 2018) - Ruff, Michael W; Buckner, Jan C; Johnson, Derek R; van den Bent, Martin J; Geurts, Marjolein
Abstract: The treatment of newly diagnosed oligodendroglioma has been revolutionized in the past decade by multiple studies demonstrating that the addition of chemotherapy to radiation therapy results in a significant survival benefit. While the most direct evidence comes from clinical trials that utilized PCV, a chemotherapy regimen consisting of procarbazine, CCNU (lomustine), and vincristine, there is circumstantial evidence suggesting that the oral agent temozolomide (TMZ), which is both better tolerated and logistically simpler than PCV, may also be effective. The lack of currently available direct comparative data for PCV vs TMZ results in a diversity of practice. In this article, Ruff and Buckner argue for PCV as part of the standard-of-care regimen for newly diagnosed anaplastic oligodendroglioma, while Geurts and van den Bent defend the use of TMZ.